Значение однонуклеотидного полиморфизма +276G/Т гена адипонектина (ADIPOQ) в формировании риска cахарного диабета 2 типа - Атраментова, Л.А.; Горшунская, М.Ю.; Караченцев, Ю.И.; Кравчун, Н.А.; Тыжненко, Т.В.; Почерняев, А.К.; Опалейко, Ю.А.; Полторак, В.В. (Фактори експериментальної еволюції організмів, 2013)
Aim. To examine the association of single nucleotide polymorphism (SNP) +276G/Т ADIPOQ gene with Type 2 diabetes mellitus in slavonic population of Kharkov – Ukrainians and Russians. Methods. SNР ADIPOQ was detected in 544 type 2 diabetic patients and 140 subjects without ischemic heart disease, arterial hypertension and diabetes. Genotyping of the SNP was performed by using the polymerase chain reaction – restriction fragments length polymorphism method. The statistical analysis was made, genotype and allele frequencies were tested by χ2. The Odds Ratio (OR) was calculated and a 95 % confidence interval (CI) was provide. Results. The genotype frequencies were consistent with Hardy-Weinberg equilibrium in both groups. Frequency of G allele is 0.69 in control group, and 0.60 in patients. The TT genotype was present in 8.6 % of control subjects, and in 16.6 % of patients (p<0.05). The TT genotype was associated with increased risk for type 2 diabetes mellitus (OR=2.00; CI 1.05-3.78; p<0,05). Homozygosity for major allele was associated with decreased risk of disease (OR=0.66;CI0,45-0,96 p<0,05). Conclusion. The TT genotype is a factor of increased risk for type 2 diabetes mellitus in the slavonic population.